Numerical simulation of thermal properties at Cu/Al interfaces based on hybrid model. Issue 3 (5th May 2015) - Tang, Yunqing; Zhang, Liqiang; Yang, Haiying; Guo, Juan; Liao, Ningbo; Yang, Ping
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate thermal properties at Cu/Al interfaces. Design/methodology/approach – A hybrid (molecular dynamics-interface stress element-finite element model (MD-ISE-FE) model is constructed to describe thermal behaviors at Cu/Al interfaces. The heat transfer simulation is performed after the non-ideal Cu/Al interface is constructed by diffusion bonding. Findings – The simulation shows that the interfacial thermal resistance is decreasing with the increase of bonding temperature; while the interfacial region thickness and interfacial thermal conductivity are increasing with similar trends when the bonding temperature is increasing. It indicates that the higher bonding temperature can improve thermal properties of the interface structure. Originality/value – The MD-ISE-FE model proposed in this paper is computationally efficient for interfacial heat transfer problems, and could be used in investigations of other interfacial behaviors of dissimilar materials. All these are helpful for the understanding of thermal properties of wire bonding interface structures. It implies that the MD-ISE-FE multiscale modeling approach would be a potential method for design and analysis of interfacial characteristics in micro/nano assembly.